Evaluation of steady-state ground resistance by field measurement and CDEGS computation - Muhammad, Usman; Zaid, Hadee; Ahmad, Nurul Nadia; Mohamad Nor, Normiza; Aman, Fazlul (Bulletin of Electrical Engineering and Informatics, 2024)
In addition to the soil resistivity and size of the grounding system, grounding system configuration can influence the steady-state resistance (RDC) of a grounding system. The RDC of four to six configurations in three distinct soil conditions (sites 1 to 3) is measured using the fall-of-potential method and computed using the current distribution, electromagnetic fields, grounding, and soil structure analysis (CDEGS) simulation. The RDC value generally decreases as size increases, i.e., when more rods or tapes are added, except for a little variation subject to the electrode arrangement and soil resistivity. The 3 and 4-parallel configurations perform better on low resistivity soil (site 1), while the grid configurations (2×2- and 3-rod grids) are better on high resistivity soil (site 2). The difference between the measured and computed values at high soil resistivity sites (sites 2 and 3) is large, ranging from 18% to 66% for site 2 and from 35% to 53% for site 3. The difference is lower and more consistent at site 1, where five out of six configurations achieve less than 10%. At all sites, the difference between computed and measured RDCs generally decreases as the area of the electrode increases, except for some cases at site 2.